2019
DOI: 10.1111/desc.12877
|View full text |Cite
|
Sign up to set email alerts
|

Maternal odor shapes rapid face categorization in the infant brain

Abstract: To successfully interact with a rich and ambiguous visual environment, the human brain learns to differentiate visual stimuli and to produce the same response to subsets of these stimuli despite their physical difference. Although this visual categorization function is traditionally investigated from a unisensory perspective, its early development is inherently constrained by multisensory inputs. In particular, an early‐maturing sensory system such as olfaction is ideally suited to support the immature visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(99 citation statements)
references
References 51 publications
(80 reference statements)
10
68
1
1
Order By: Relevance
“…In conclusion, the present results indicate that olfaction plays an important role in young infants’ perception of their social partners and they are consistent with findings showing that the mother's body odor can also shape face categorization by enhancing a face‐selective electro‐encephalographic response in the infant brain (Leleu et al, ). Findings such as these add to a growing body of evidence indicating that multisensory interaction has a pervasive influence on behavior in early human development (Lewkowicz, ).…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, the present results indicate that olfaction plays an important role in young infants’ perception of their social partners and they are consistent with findings showing that the mother's body odor can also shape face categorization by enhancing a face‐selective electro‐encephalographic response in the infant brain (Leleu et al, ). Findings such as these add to a growing body of evidence indicating that multisensory interaction has a pervasive influence on behavior in early human development (Lewkowicz, ).…”
Section: Discussionsupporting
confidence: 92%
“…Bayet et al, 2017;Heck, Hock, White, Jubran, & Bhatt, 2016;Safar & Moulson, 2020). Furthermore, prior studies showing an impact of maternal odor on face processing investigated infants at 4 months of age (Durand et al, 2013(Durand et al, , 2020Leleu et al, 2019), showing that maternal odor influences face processing per se already at an earlier age than investigated here.…”
Section: Future Directions and Limitationsmentioning
confidence: 50%
“…Three recent studies have suggested a modulation of infant face processing in general by the presence of maternal odor (Durand et al, 2013(Durand et al, , 2020Leleu et al, 2019). Most importantly, Leleu et al (2019) found an enhanced neural response to faces in the presence of maternal odor. While their work thereby shows a modulation by maternal odor of face processing per se, the present result suggest that maternal odor can furthermore impact neural responses to specific aspects of face processing.…”
Section: Maternal Odor As a Momentary Modulator Of Infants' Responsesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a further challenge, in experiments conducted with 4-to 6-month-old infants, natural images of faces were displayed embedded among a stream of common objects, and in a second experiment, phase scrambled versions of the faces and objects were displayed (de Heering & Rossion, 2015). A clear response at the base stimulation frequency was observed for faces but not for the phase-scrambled versions, and this response was present to a greater degree over the RH than LH (see also Leleu et al, 2019). These findings led to the conclusion that selective processes for face processing are present well before word recognition is acquired and hence cannot possibly be the outcome of the hemispheric competition and cooperation that ensues over development.…”
Section: The Role Of Literacy Acquisition As the Trigger For Lateralimentioning
confidence: 99%